Bisnis Islam Terhadap Loyalitas Konsumen di Industri Ritel - Mohammad Syaiful Su'ib; Tri Muhammad Abdullah Rizky (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study was conducted to evaluate the application of Islamic business ethics in retail stores in Sumberanyar, Probolinggo, with a focus on price transparency and customer service. The purpose of this study is to determine the extent to which the principles of Islamic business ethics are applied by retailers and their impact on consumer satisfaction. The method used in this research is to interview consumers from three retail stores in Sumberanyar, namely Zaini Store, Harapan Jaya Store and Yeni Store, and to analyse the data obtained from these interviews. The results show that Harapan Jaya Store stands out in the application of price transparency and customer service with a score of 70% each, indicating a good application of Islamic business ethics. Meanwhile, Yeni Store has weaknesses in price transparency (65%), although it is quite good in customer service (70%). Zaini Store excels in price transparency (70%) but has a weakness in customer service (60%) due to limited staff. The results suggest that although Islamic business ethics are applied, differences in their application affect customer satisfaction and loyalty, with internal factors such as management and staff training strongly influencing service quality.